KEPASTIAN HUKUM TERHADAP KEWENANGAN MAJELIS KEHORMATAN NOTARIS TERKAIT PENGAMBILAN FOTOKOPI MINUTA AKTA DAN PEMANGGILAN NOTARIS OLEH PENYIDIK PENUNTUT UMUM DAN HAKIM - Etin Mintarsih; Dhody. AR. Widjaja Atmadja; Achmad Fitrian (Journal of Innovation Research and Knowledge, 2025)
Legal certainty on the authority of the notary honorary council (MKN) in making photocopies of deed minutes and summoning notaries by law enforcement officers is needed to maintain a balance between the protection of the notary profession and law enforcement. However, the vagueness of the procedure and the limitation of the MKN's authority are still obstacles in practice. This study analyzes the legal certainty of MKN authority and its impact on the protection of notaries and the effectiveness of the legal system in Indonesia. This study raises two problems, namely how the analysis of the authority of the notary honorary council related to The Taking of photocopies of minutes of deed and summons of notary by the public prosecutor and Judge investigators and how the legal certainty of the authority of the notary honorary council related to The Taking of photocopies of minutes of deed and summons of According to Philipus m Hadjon and The Theory of legal certainty according to Jan Michiel Otto. The method used in this study is a type of normative juridical research that is legal research literature or secondary data with sources of primary, secondary, and tertiary legal materials. The research approach used is legislation approach, case approach, analytical approach, conceptual approach and legal material collection techniques carried out by identifying and inventorying positive legal rules, book literature, journals, and other sources of legal materials. For the technique of analysis of legal materials is carried out by the interpretation of the law: 1) grammatical interpretation, 2) systematic interpretation and methods of legal Construction: 1) construction of analogy, 2) construction of legal refinement. The results showed that the honorary council of Notaries (MKN) play a role in granting or denying permission for investigators, prosecutors, or judges to take a photocopy of the minutes of the deed or call a notary, in order to maintain the confidentiality of the deed and protect the rights of notaries in accordance with Article 66 UUJN. The application for permission must be submitted to MKN before the action is carried out. However, there are still legal uncertainties regarding the mechanism and limits of MKN's authority, because the regulations are not completely clear. This can hinder the investigation and judicial process if the MKN decision is not given quickly and clearly. On the other hand, the protection of notaries remains necessary to prevent abuse of authority by law enforcement officers.